China and the rules of engagement in Antarctica - Julia Jabour (2017)
Chinese repudiation of the rule of law in the Philippines v. China case resulted in, among other things, speculation about the country’s perceived – or real – interests and activities in Antarctica, where Australia has significant investment, and where respecting the rules of engagement with international law is paramount.